2002
DOI: 10.1046/j.1464-5491.2002.00762.x
|View full text |Cite
|
Sign up to set email alerts
|

Gliclazide improves anti‐oxidant status and nitric oxide‐mediated vasodilation in Type 2 diabetes

Abstract: Gliclazide reduces oxidative stress in Type 2 diabetic patients by improving plasma anti-oxidant status. This effect is associated with enhanced NO-mediated vasodilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 23 publications
0
43
0
2
Order By: Relevance
“…In type 2 diabetic patients, it was reported that gliclazide treatment delayed the progression of diabetic nephropathy only, whereas it produced no significant effect on the development or progression of retinopathy or macrovascular complications (Patel et al, 2008). These findings are very important because gliclazide is one of the few hypoglycemic agents with an antioxidant effect (Fava et al, 2002). It is evident from the different aforementioned hyperglycemia-induced mechanistic pathways and the data (both experimental and clinical) presented in this section that the pathogenesis of diabetic complications is a complex process.…”
Section: Does Reduced or Intensive Therapy Of Hyperglycemia Prevent Dmentioning
confidence: 89%
See 1 more Smart Citation
“…In type 2 diabetic patients, it was reported that gliclazide treatment delayed the progression of diabetic nephropathy only, whereas it produced no significant effect on the development or progression of retinopathy or macrovascular complications (Patel et al, 2008). These findings are very important because gliclazide is one of the few hypoglycemic agents with an antioxidant effect (Fava et al, 2002). It is evident from the different aforementioned hyperglycemia-induced mechanistic pathways and the data (both experimental and clinical) presented in this section that the pathogenesis of diabetic complications is a complex process.…”
Section: Does Reduced or Intensive Therapy Of Hyperglycemia Prevent Dmentioning
confidence: 89%
“…This is evidenced by the elevated levels of thiobarbituric acid reactive substances and reduced erythrocyte GSH (Seghrouchni et al, 2002). In type 2 diabetic patients, treatment with gliclazide for 12 weeks ameliorated oxidative stress better than did glibenclamide (Fava et al, 2002). Available data from DCCT and Epidemiology of Diabetic Complications and Interventions (EDIC) Trial indicated that type 1 diabetic patients in the intensive therapy group still had increased levels of protein glycation products and AGEs despite intensive treatment .…”
Section: Does Reduced or Intensive Therapy Of Hyperglycemia Completelmentioning
confidence: 99%
“…Thirdly, eight patients (42%) were taking sulphonylurea. This is another interesting point, as gliclazide has been shown to have a protective effect on the endothelium [4].…”
mentioning
confidence: 93%
“…This hypothesis can be supported by many observations which suggest that the activity of oral betacytotropic drugs is pleiotropic and not limited solely to the stimulation of beta cells. They produce many other therapeutically positive effects, among them a decrease in insulin resistance (Almer 1984;Fava et al 2002;Gram et al 1988;Itoh et al 2003;Jennings et al 1992;O'Brien et al 2000). This may also involve the activity of the CGT system.…”
Section: Introductionmentioning
confidence: 99%